2006
DOI: 10.1007/s11882-006-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenoidectomy and tympanostomy tubes in the management of otitis media

Abstract: Otitis media is one of the most common childhood infections and the most frequent cause for antibiotic prescriptions in children. As respiratory infections are also associated with childhood asthma, children with recurrent otitis media or with persistent middle-ear effusion are also at an increased risk for developing asthma, which should be appreciated when a child with middle-ear disease is evaluated. The first choice of surgery in chronic middle-ear inflammatory disease is the insertion of tympanostomy tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…This could have led to recall bias. The risk of other bias was classified as unclear for five studies [10][11][12]18,52,53 and low for the remaining four studies. [15][16][17]20 Overall we concluded that eight studies [10][11][12][15][16][17]20,52 were at a low risk of bias and two 18,21 were at a moderate risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…This could have led to recall bias. The risk of other bias was classified as unclear for five studies [10][11][12]18,52,53 and low for the remaining four studies. [15][16][17]20 Overall we concluded that eight studies [10][11][12][15][16][17]20,52 were at a low risk of bias and two 18,21 were at a moderate risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…This results in continuous mouth breathing, sleep disturbances, and long-term effects on the growth of the facial skeleton and teeth [13]. Thereby, adenoidectomies are also performed in cases of nasopharyngeal obstruction without any evident history of recurrent or persistent otitis media [14].…”
Section: Introductionmentioning
confidence: 99%
“…COME is defined as the persistence of middle ear fluid beyond 12 weeks and has multiple causes, including environmental and host factors. 1,2 Medical treatment is the first choice of management, but it does not have a standard. It usually includes eradication of upper respiratory tract infections, control of allergy, and environmental precautions.…”
mentioning
confidence: 99%